PENGARUH PELAYANAN MARKETING TERHADAP LOYALITAS NASABAH PADA PT BPR CAHAYA FAJAR - Vina Andita Pratiwi; Eman Sulaiman; Niko Stevanus Lukman (LPPM STAI DARUSSALAM LAMPUNG, 2020)
The purpose of this study was to determine the Marketing Services of PT. BPR Cahaya Fajar Cirebon, To find out the Customer Loyalty of PT. BPR Cahaya Fajar Cirebon, and to determine the effect of Marketing Services on Customer Loyalty at PT. BPR Cahaya Fajar Cirebon. The population in this study was 3,152 loan customers. The sampling technique uses a simple random technique with a sample of 100 customers. The results showed that there was a strong and significant positive effect between Marketing Services on Customer Loyalty of PT. BPR Cahaya Fajar Cirebon. Partial test results (t test) note that the independent variable Marketing Services has a positive and significant effect on the Customer Loyalty variable because both variables have a Sig value of 0.05,